Identifikasi Digital Literacy untuk mengukur kesiapan Jurnalisme Warga - Budi Susanto; Umi Proboyekti (Annual Research Seminar (ARS), 2016)
Villages in Bantul are the essential subjects in implementing the Rural Information System (SID) of Bantul. Hence, the ability of using information and communication technology (ICT) is the main requirement. Citizen journalism using ICT is one of the must-have skilled to implement e-goverment in village level. In order to prepare them for using the SID, an assessment of digital literacy is conducted to measure their knowledge and skill in using ICT. The three essential skill for ICT citizen journalism are accessing WWW, using email services, and using word processing application. The 37 respondents from six villages which proposed to implement SID underwent the digital literacy assessment. The result stated that average 76.36% for WWW access skill, 64.39%for using email and 73% for word processing application, whereas passing score is 85%. Therefore, all average scores are below standard passing score. Based on the results, the recommendation is the enhancement of villagers' ICT skill is required and prioritized.